Sleep apnea and autonomic dysfunction in patients with dementia - Michelle Herberts; Bhanuprakash Kolla; Travis Paul; Praveen Mekala; Meghna P. Mansukhani (Frontiers in Neuroscience, 2022)
Sleep apnea is common sleep disorder that is associated with an is an increase in risk of many health conditions, including systemic hypertension, stroke, atrial fibrillation, and heart failure. The predominant underlying pathophysiological mechanism for elevated risk of these conditions in patients with sleep apnea is thought to involve autonomic dysfunction in the form of sympathetic overactivity. Autonomic dysfunction is also associated with several neurodegenerative disorders and sleep apnea, in turn, has been shown to be associated with an increased risk of development of mild cognitive impairment and various types of dementia. Rapid eye movement sleep behavior disorder, which is also associated with an increased risk of alpha synucleiopathy-related dementia, is also linked with autonomic dysfunction. In this article we explore the relationship between sleep apnea, autonomic dysfunction, rapid eye movement sleep behavior disorder and dementia. This article describes the various autonomic dysfunction that are thought to occur in the context of sleep apnea. And illustrate the mechanisms by which sleep apnea, through its impact on autonomic dysfunction could potentially result in dementia. We also review the evidence examining the impact of treatment of sleep apnea on autonomic dysfunction and cognitive outcomes.